A Feasibility Study on Segre Waste - Dunuan, Lara Mia (College of Engineering, 2003)
It is a fact that proper garbage disposal is one of the perennial problems that the government is facing. Metro Manila alone generates 6,000 tons of garbage daily. There is a need to segregate garbage. Although the government, through the MMDA imposed regulations about segregation already, new problems arise. The concerned people find it often cumbersome to segregate their garbage. With these problems at hand, the SegreWaste is introduced. The SegreWaste is the first garbage bin to be introduced in the Philippines with a compartment for biodegradable wastes and a separate compartment for non-biodegradable wastes. Strengthened by the high acceptance level result of the survey conducted, the target market shall be all NCR households with a minimum annual income of P100,000. To ensure sales, appropriate marketing strategies will be employed. Product strategies include giving the product a catchy name, proper packaging, and releasing it in trendy colors. The pricing strategy that will be used will be the going rate. For placement, the product will also be sold directly to the malls and trucks will be used to deliver. Posters, brochures, and sponsoring seminars will be used as promotions for the product. For the five years, the marketing budget is P 3,31,404. If one unit cost P250, based on the projected demand the sales for the first year is P 25,435,500. Total sales for the five years are P300,601,026. The product will be manufactured in-house with some minor parts to be outsourced. Injection molding is the process to be applied for the manufacturing of the SegreWaste. Polypropylene is chosen as the major raw material due to its availability quality suppliers and customers. Given the start-up, manufacturing and administrative costs of the project, the total project cost is P 9,217,202.32. Part of the project cost will be financed by the Development Bank of the Philippines' Micro-Finance Division. The remaining balance will be from stocks. The financial statements presented in this study, show a positive and increasing trend In the company's net income and cash flow projections throughout the five-year operating period. Moreover, the financial ratios used indicate a stable financial position for the company. From the sensitivity analysis, the same conclusion can be made since the breakeven values can be obtained were less than the projected values for sales, price, and volume. Also, the computed net present value and internal rate of return prove that the project is an acceptable venture. The payback period is 1.25 years. This suggests that the investment is recovered early in the company's life. Aside from benefiting the company and the target market, the project venture also has some benefits to the community. This includes the generation of jobs, the patronization of local suppliers, and the implementation of the Waste Segregation Scheme in the NCR households. Additional benefits also include the municipal tax, corporate income tax, and personal income tax which result from the project. These taxes shall also contribute to the local and national government. These taxes will be used to fund various projects for the country. Furthermore, qualitative benefits, like the motivation of other inventors and innovators, the promotion of cleanliness in households, and easier and more manageable jobs for the garbage collectors have also been identified. There are no other significant disbenefits which can be attributed to the venture other than minor waste generation since recycling shall be employed. The combined results of the four parts of the feasibility study point to the same conclusion - the project venture is feasible.